On the regularity of metonymy across languages (exemplified on some metonymies in medical discourse) - Brdar Mario (ExELL (Explorations in English Language and Linguistics))
The topic of metonymy regularity has cropped up in several recent articles, a welcome sign of growing interest in this phenomenon, which may eventually contribute towards shedding more light on the phenomenon of metonymic competence, paralleling metaphoric competence (Littlemore & Low, 2006). However, in order to deal with this complex phenomenon one should be clear about the circumstances of the use of metonymy. Two issues pertaining to the use of metonymy that play a central role in Slabakova, Cabrelli Amaro & Kang (2013 & 2016) are mentioned in the very title of their study—novel metonymy and regular metonymy. In this article I draw attention to some problems with the assumption that these are opposites of each other and then examine what Slabakova, Cabrelli Amaro & Kang consider to be regular metonymy. I demonstrate that while their novel metonymies are not really so different from the regular ones, there is another sense of metonymy regularity in cognitive linguistics, where metonymy seems to come closest it can to novelty. This phenomenon, referred to as regular metonymy, logical metonymy or logical polysemy, crosses boundaries of languages and cultures. This is illustrated on several sets of examples from medical discourse in a number of languages.